Penentuan Zona Wisata Bahari Pantai Rupat Utara Menggunakan Sistem Informasi Geografi - Roni Salambue (Annual Research Seminar (ARS), 2016)
North Rupat beach has been designated as one of tourism areas by the district of Bengkalis. Some strategic policies used in supporting Rupat beach as a marine tourism destination are  building infrastructure access roads, harbors, crossing ferry and accomodation. This research aims to determine the marine tourism zoning at North Rupat Beach using Geographic Information System (GIS). The methods used is Multi Criteria Evaluation of the suitability of the area in GIS. The analysis results showed that areas of Teluk Rhu, Tanjung Punak and Putri Sembilan were suitable enough for coastal marine tourism. The areas of Teluk Rhu and Tanjung Punak were suitable for recreation marine tourism beaches, while on the other hand Putri Sembilan was not.